2013
DOI: 10.1104/pp.113.214940
|View full text |Cite
|
Sign up to set email alerts
|

AUXIN RESPONSE FACTOR17 Is Essential for Pollen Wall Pattern Formation in Arabidopsis      

Abstract: In angiosperms, pollen wall pattern formation is determined by primexine deposition on the microspores. Here, we show that AUXIN RESPONSE FACTOR17 (ARF17) is essential for primexine formation and pollen development in Arabidopsis (Arabidopsis thaliana). The arf17 mutant exhibited a male-sterile phenotype with normal vegetative growth. ARF17 was expressed in microsporocytes and microgametophytes from meiosis to the bicellular microspore stage. Transmission electron microscopy analysis showed that primexine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 58 publications
1
116
0
Order By: Relevance
“…According to their functions, these ARFs are divided into two classes: transcriptional activators and transcriptional repressors (Guilfoyle and Hagen, 2007). Many investigations have revealed the essential roles of ARFs in plant growth and development as well as in stress adaptation (Hardtke and Berleth, 1998;Nemhauser et al, 2000;Ellis et al, 2005;Okushima et al, 2005aOkushima et al, , 2005bWang et al, 2011;Yang et al, 2013). In this study, we demonstrate that ARF2 participates in the regulation of K + uptake.…”
Section: Introductionsupporting
confidence: 50%
“…According to their functions, these ARFs are divided into two classes: transcriptional activators and transcriptional repressors (Guilfoyle and Hagen, 2007). Many investigations have revealed the essential roles of ARFs in plant growth and development as well as in stress adaptation (Hardtke and Berleth, 1998;Nemhauser et al, 2000;Ellis et al, 2005;Okushima et al, 2005aOkushima et al, , 2005bWang et al, 2011;Yang et al, 2013). In this study, we demonstrate that ARF2 participates in the regulation of K + uptake.…”
Section: Introductionsupporting
confidence: 50%
“…AUXIN RESPONSE FACTOR 17 (ARF17) controls callose biosynthesis and primexine deposition by directly modulating the expression of CalS5 and RPG1 [102]. In flowering plants, GA regulates pollen wall development via GAMYB [81,84], and GAMYB activates targets such as CYP703A3 [81], and the double mutant rga-28 gai-td1, which is defective in the key GA signaling repressor DELLA proteins, displays defective pollen wall development [103].…”
Section: Other Regulatorsmentioning
confidence: 99%
“…ARF17 , an auxin responsive factor, plays a major role in plant fertility by regulating primexine deposition. The arf17 mutant shows defective callose formation, a total absence of primexine and pollen degeneration (Yang et al ). In addition, it has been demonstrated that ARF17 directly regulates CalS5expression (Yang et al ).…”
Section: Anther and Pollen Developmentmentioning
confidence: 99%
“…The arf17 mutant shows defective callose formation, a total absence of primexine and pollen degeneration (Yang et al ). In addition, it has been demonstrated that ARF17 directly regulates CalS5expression (Yang et al ). CalS5 expression is also reduced in the defective in exine formation1 ( dex1) mutant; this gene encodes for a plasma membrane protein, which is highly conserved in higher plants such as rice, barley and Brachypodium (Ma et al ) (Table ).…”
Section: Anther and Pollen Developmentmentioning
confidence: 99%